Cadmium, NAG activity, and beta 2-microglobulin in the urine of cadmium pigment workers. - Kawada, T (1989)
Cadmium (Cd), N-acetyl-beta-D-glucosaminidase (NAG) activity, beta 2-microglobulin (BMG), and creatinine (cr) in urine were measured during April and September 1986 in workers exposed to cadmium pigment dust (maximum exposure 3.0 micrograms/m3/8 h for respirable dust). In April and September urinary Cd ranged from 0.2 to 9.5 and from 0.5 to 7.0 micrograms/g cr with a geometric mean of 0.7 and 1.2 micrograms/g cr, respectively. The correlation coefficient between Cd and NAG was 0.261 (n = 61) in April and 0.389 (n = 50) in September. The correlation coefficient between Cd and BMG was 0.241 (n = 63) in April and 0.115 (n = 50) in September. It appears that urinary Cd concentrations have a closer relation with urinary NAG than urinary BMG, even when urinary Cd concentrations are less than 10 micrograms/g cr. It is concluded that NAG is a more sensitive indicator of Cd absorption than BMG even at urinary Cd concentrations of less than 10 micrograms/g cr.